2012
DOI: 10.1016/j.jep.2012.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Old formula, new Rx: The journey of PHY906 as cancer adjuvant therapy

Abstract: Over a ten-year period, the multiplex technology "PhytomicsQC" has been used to show batch-to-batch consistency of PHY906 production. Advanced clinical trials are ongoing to demonstrate the effectiveness of PHY906 as adjuvant therapy for cancer patients undergoing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 41 publications
4
89
0
1
Order By: Relevance
“…It has been used for over 1800 years to treat a variety of gastrointestinal symptoms including diarrhea, nausea and vomiting, and abdominal cramps (12,60). PHY906 is a modified pharmaceutical preparation derived from the traditional herbal formulation Huang-qin-tang and it consists of the same four herbs as Huang-qin-tang at a relative weight ratio of 3:2:2:2 (12).…”
Section: Huang-qin-tangmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used for over 1800 years to treat a variety of gastrointestinal symptoms including diarrhea, nausea and vomiting, and abdominal cramps (12,60). PHY906 is a modified pharmaceutical preparation derived from the traditional herbal formulation Huang-qin-tang and it consists of the same four herbs as Huang-qin-tang at a relative weight ratio of 3:2:2:2 (12).…”
Section: Huang-qin-tangmentioning
confidence: 99%
“…Furthermore, they have conducted a series of preclinical and clinical studies to investigate the anticancer activities of PHY906 in recent years. In vivo studies, the combination of PHY906 with irinotecan, capecitabine, 5-FU, and leucovorin (LV) resulted in significant improvement in gastrointestinal toxicities, antitumor activity, and overall survival with no increased host toxicity versus chemotherapeutics alone (60). In the case of irinotecan, for which severe delayed-onset diarrhea is the major dose-limiting toxicity, PHY906 could effectively regulate intestinal bacteria, alleviate diarrhea and reduce drug-induced mortality in mice.…”
Section: Huang-qin-tangmentioning
confidence: 99%
See 1 more Smart Citation
“…Josephine Briggs, head of the National Center for Complementary and Integrative Health in National Institute of Health, commented about the formula PHY906 (Huangqin Decoction, 黄芩汤) being an adjuvant to chemotherapy in patients with colon cancer. (55) Information given in this paper emphasizes that CMM formula is not a simple "polypharmacy." Like any formulation, CMM has its advantages and disadvantages.…”
Section: Strategy Suggestions For Study On Cmm and Its Formulamentioning
confidence: 99%
“…A promising case that was found in clinical trials, is PHY906, a herbal product derived from Scutellaria baicalensis Decoction (Huang-Qin-Tang in Chinese). A series Phase I/II clinical trials have concluded its efficacy in reducing gastrointestinal toxicity and in enhancing tumor response in cancer patients receiving chemotherapy [12]. In addition to these cases, a lot of Chinese medicinal ingredients or herbal extracts have been proven effective in reducing the side-effects of chemotherapy and reversion resistance, such as codonopsis pilosula, Astragalus, Scutellaria baicalensis, ginsenoside, berberine and curcumin [13][14][15][16].…”
Section: New Strategy In Chemotherapy: Combination Of Other New Medicmentioning
confidence: 99%